Effects of loading rate and notch-to-depth ratio of notched beams on flexural performance of ultra-high-performance concrete. (October 2017) - Meng, Weina; Yao, Yiming; Mobasher, Barzin; Khayat, Kamal Henri
Abstract: This paper addresses the effects of loading rate and notch-to-depth ratio on flexural properties of ultra-high-performance concrete (UHPC) notched beam specimens, in order to enable use of standardized laboratory test data to predict flexural properties of UHPC structures that have different dimensions and are subjected to a range of loading rates. UHPC notched beams were tested in three-point bending to study the effects of three notch-to-depth ratios of 1/6, 1/3, and 1/2 at five loading rates of 0.05, 0.50, 1.25, 2.50, and 5.00 mm/min on flexural performance. Test results indicate that loading rate and notch-to-depth ratio have significant effects on flexural properties of the UHPC notched beams. The flexural strength is shown to increase with the loading rate and the notch-to-depth ratio. The fracture energy increases with the loading rate but decreases with the notch-to-depth ratio. The changes of flexural properties with the loading rate are also dependent on the notch-to-depth ratio. Regression analyses to correlate flexural properties associated with the loading rate and notch-to-depth ratio were conducted to obtain parameters for UHPC structures.